Deadly Assets - Griffin, W. E. B.; Butterworth, William E (William Edmund) (New York : G.P. Putnams Sons, 2015)
"In Philadelphia--suffering among the countrys highest murder rates--the tension between the Philadelphia Police Department and its Citizens Oversight Committee has long been reaching a boiling point. That turmoil turns from bad to worse shortly after the committee begins targeting police shootings--especially those of twenty-seven-year- old Homicide Sergeant Matt Payne, the Wyatt Earp of the Main Line--and then the committees combative leader is found shot dead point-blank on the front porch of his run- down Philly row house. As chanting protesters fill the streets, the city threatens to erupt"--Provided by publisher.
Keywords: Payne, Matt (Fictitious character) -- Fiction; Police -- Pennsylvania; Philadelphia; Fiction; Murder -- Investigation; Fiction; Philadelphia (Pa.) -- Fiction; Detective and mystery fiction